Child Neurology: Hemiconvulsion-Hemiplegia-Epilepsy Syndrome in the Setting of COVID-19 Infection and Multisystem Inflammatory Syndrome. (25th October 2022) - Gong, Paul; Karakas, Cemal; Morgan, Bethanie
Abstract : Hemiconvulsion-hemiplegia-epilepsy (HHE) syndrome is a rare pediatric epilepsy syndrome characterized by prolonged focal febrile convulsive status epilepticus with unilateral hemispheric cerebral edema, followed by the subsequent development of hemiplegia, global atrophy of the affected hemisphere, and epilepsy. The pathophysiology of HHE syndrome remains poorly understood though is clearly multifactorial. Factors thus far implicated are hyperthermia, proinflammatory state, and cytotoxic edema from prolonged ictal activity. Prognosis is variable, from the resolution of hemiplegia and seizures to permanent hemiparesis and refractory epilepsy. We describe a 2-year-old boy who presented with superrefractory focal status epilepticus in the setting of acute coronavirus infectious disease-2019 (COVID-19) and multisystem inflammatory syndrome in children (MIS-C). He had right-sided hemiplegia on neurologic examination, and an MRI examination of the brain showed left cerebral hemispheric edema consistent with HHE syndrome. Our case represents the first report in the literature on HHE syndrome in the setting of acute COVID-19 and MIS-C.